Loop Anchor Tension Band Technique for Patella Fractures Lowers the Rate of Kirschner Migration. Issue 6 (June 2021) - Yao, Shu-Hsin; Lin, Shu-Fan; Lin, Chang-Hao; Chen, Chun-Ho
Hightlights: Painful irritation due to migrated Kirschner wire is the most common complication in the traditional tension band wiring group. Loop anchor tension band technique is reproducible and easy to perform. Loop anchor tension band technique significantly reduced the implants dislodgement rate compared to traditional tension band wiring method Abstract: Objective: To compare the complications of patella fracture after open reduction and internal fixation using our innovative, loop-based modification of the tension band wiring technique and the traditional tension band wiring technique. Methods: Fifty-eight patients with patella fracture (AO/OTA: 34-C) were enrolled in this retrospective case-control study during the study period. We treated 36 patients with the traditional tension band wiring and 22 patients with our loop anchor tension band technique. Lysholm knee scoring scale, sex, numbers of wire dislodge, number of implants removal between two groups were compared. Results: The number of cases of wire dislodgement was zero in the loop anchor tension band group and seven in the traditional tension band group. There was statistically significant difference (P = 0.037). Lysholm knee score (P = 0.685) and operation time (P = 0.395) were not significantly different between the two groups Conclusions: The loop anchor tension band technique is safe and effective for treating patella fractures. The rates of implant loosening and wire pull-out were significantly lower in the loop anchor tension band group than those in the traditional technique group.